The Engagement of Complementors and the Role of Platform Boundary Resources in e-Commerce Platform Ecosystems - Martin Engert; Julia Evers; Andreas Hein; Helmut Krcmar (Information Systems Frontiers, 2022)
Abstract The success of digital platforms can be attributed to the engagement of autonomous complementors as exemplified by e-commerce Content Management System (CMS) platforms such as WordPress and Shopify. Platform owners provide Platform Boundary Resources (PBRs) to stimulate and control complementor engagement. Despite the increasing scholarly interest in digital platform ecosystems, their exact role in facilitating and channeling complementor engagement remains unclear. Therefore, we conducted an embedded case study on CMS platform ecosystems, comprising a total of 24 interviews with platform owners and complementors. We inductively derive five types of complementor engagement and their respective manifestations and two overarching engagement goals of complementors. Moreover, we determine the different types of PBRs utilized, including their critical effects, and distinguish between uniform and individual PBRs reflecting their respective generalizability and scalability. We discuss the findings by introducing the concepts of complementor resourcing and complementor securing and shed light on the standardization-individualization tension of PBRs faced by platform owners.
Keywords: 330; Digital platform ecosystems; Complementor engagement; Platform boundary resources; Content management systems; e-Commerce; Case study